Genomic dynamics of species and mobile genetic elements in a prolonged blaIMP-4-associated carbapenemase outbreak in an Australian hospital. (20th January 2020) - Kizny Gordon, A; Phan, H T T; Lipworth, S I; Cheong, E; Gottlieb, T; George, S; Peto, T E A; Mathers, A J; Walker, A S; Crook, D W; Stoesser, N
Abstract: Background: Hospital outbreaks of carbapenemase-producing organisms, such as bla IMP-4 -containing organisms, are an increasing threat to patient safety. Objectives: To investigate the genomic dynamics of a 10 year (2006–15) outbreak of bla IMP-4 -containing organisms in a burns unit in a hospital in Sydney, Australia. Methods: All carbapenem-non-susceptible or MDR clinical isolates (2006–15) and a random selection of equivalent or ESBL-producing environmental isolates (2012–15) were sequenced [short-read (Illumina), long-read (Oxford Nanopore Technology)]. Sequence data were used to assess genetic relatedness of isolates (Mash; mapping and recombination-adjusted phylogenies), perform in silico typing (MLST, resistance genes and plasmid replicons) and reconstruct a subset of bla IMP plasmids for comparative plasmid genomics. Results: A total of 46/58 clinical and 67/96 environmental isolates contained bla IMP-4 . All bla IMP-4 -positive organisms contained five or more other resistance genes. Enterobacter cloacae was the predominant organism, with 12 other species mainly found in either the environment or patients, some persisting despite several cleaning methods. On phylogenetic analysis there were three genetic clusters of E. cloacae containing both clinical and environmental isolates, and an additional four clusters restricted to either reservoir. bla IMP-4 was mostly found as part of a cassette array ( blaIMP-4 -qacG2-aacA4-catB3 ) in a class 1 integron within a previously described IncM2 plasmid (pEl1573), with almost complete conservation of this cassette across the species over the 10 years. Several other plasmids were also implicated, including an IncF plasmid backbone not previously widely described in association with bla IMP-4. Conclusions: Genetic backgrounds disseminating bla IMP-4 can persist, diversify and evolve amongst both human and environmental reservoirs during a prolonged outbreak despite intensive prevention efforts.